Performance analysis in sport and soccer: Past, present and future – narrative review - McGillick, Connor; Towlson, Chris; Barrett, Steve; Toner, John (Journal of Sports Research, 2024)
As performance analysis (PA) in sport and soccer has developed, numerous methods of analysis are available to provide objective video and data insights on performances. The purpose of this narrative review is to discuss PA in sport and soccer, critically appraise past and present PA techniques and preview the future of PA to enhance knowledge and inform PA practices. The methodology featured a literature review of key research papers within the areas of manual and computerised notational analysis, manual and computerised time motion analysis, wearable technology, stadium infrastructure, artificial intelligence and ethical considerations of PA. The findings of this review determined there are varied methods of PA available to practitioners to conduct technical, tactical and physical analysis within sport and soccer. Each technique features varied workflows and budget requirements which influence process advantages, disadvantages and accessibility. The evaluation of methods allowed the review to determine a decision-making matrix that can be used by practitioners to identify the most applicable PA procedures related to their resources, infrastructure and analytical aims. Alongside the decision-making matrix, the review also found that there are key ethical considerations regarding the delivery of PA insights. Given the wide array of PA tools available, and artificial intelligence influences likely to increase in the future, practitioners need to carefully consider what analysis is conducted, when insights are delivered and how information is provided to ensure effective, ethical practices.